Structure and viscoelastic behavior of pharmaceutical biocompatible anionic microemulsions containing the antitumoral drug compound doxorubicin - Formariz, T. P. [UNESP]; Chiavacci, Leila Aparecida [UNESP]; Scarpa, M. V. [UNESP]; Silva-Junior, A. A. [UNESP]; Egito, E. S. T.; Terrugi, C. H. B. [UNESP]; Franzini, C. M. [UNESP]; Sarmento, V. H. V.; Oliveira, Anselmo Gomes de [UNESP] (Elsevier B.V., 2010)
Structure and viscoelastic properties of negatively charged oil-in-water (o/w) microemulsions have been investigated. Microemulsions (ME) containing soya phosphatidylcholine (SPC), eumulgin HRE 40 ( EU) and sodium oleate (SO) as surfactant, cholesterol (CHO) as oil phase, and aqueous buffer with and without the antitumoral doxorubicin (DOX) have been studied. The effect of the oil phase/surfactant ratio (O/S) and the DOX incorporation on the structural and rheological properties have been studied in several compositions of ME systems. The rheological analyses were performed through the oscillation stress sweep, creep recovery test, and viscosity test. The combination of the DOX incorporation with the high O/S ratio provided a further viscoelastic structure with linear behavior. Independently of the O/S ratio the oil phase diameter increases according to a sigmoid profile, stabilizing up to 340 min. The apparent viscosity decreases a minimum value with the shear rate, but increases with both the O/S ratio and the DOX incorporation in the system. The structural and rheological properties of the studied MEs were directly dependent on the O/S ratio and can be used to improve the application of the system in the pharmaceutical field. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Microemulsion; Doxorubicin; Rheological analyses; Cholesterol; Storage modulus